2007
DOI: 10.1144/sp278.9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental changes at the Frasnian–Famennian boundary in Central Morocco (Northern Gondwana): integrated rock-magnetic and geochemical studies

Abstract: Rock magnetic (magnetic susceptibility and hysteresis parameters) and geochemical analyses (major and trace elements) were carried out on whole rock samples of two Frasnian–Famennian boundary sections, Anajdam and Bou-Ounebdou in the Central Morocco (Western Meseta). During the Frasnian, the decreasing trend of the magnetic susceptibility signal, mainly carried by low-coercivity magnetite grains, indicates a gradual reduction of detrital influx. This decrease in detrital input parallels a Frasnian long-term se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 80 publications
(82 reference statements)
1
5
0
Order By: Relevance
“…The higher concentration of Zn in the middle unit indicates high organic matter ux and reducing conditions (Tribovillard et al, 2006). A higher Si/Al ratio in the middle unit re ects the clastic in ux with high to moderate energy condition (Riquier et al, 2007). It also supports the concept of high biological productivity in the middle unit as compared to the upper and lower units.…”
Section: Geochemical Analysissupporting
confidence: 60%
“…The higher concentration of Zn in the middle unit indicates high organic matter ux and reducing conditions (Tribovillard et al, 2006). A higher Si/Al ratio in the middle unit re ects the clastic in ux with high to moderate energy condition (Riquier et al, 2007). It also supports the concept of high biological productivity in the middle unit as compared to the upper and lower units.…”
Section: Geochemical Analysissupporting
confidence: 60%
“…While the LKE and UKE are first and foremost biotic crises (McGhee 1988, Bambach et al 2004, Stigall 2012, assembling detailed species richness data from many sections would be labor intensive. Wide varieties of geochemical data are available across the F-F interval, including elemental data that serve as proxies for detrital input, productivity, and redox conditions (Over et al 1997;Riquier et al 2006Riquier et al , 2007Whalen and Day 2008;Boyer et al 2011;Whalen et al 2015). However, many of these proxies vary with depositional setting, hampering their use as global markers (Algeo and Rowe 2012).…”
Section: C Excursions and Defining The F-f Eventsmentioning
confidence: 99%
“…For two of the studied sections (the Beringhauser Tunnel section in the Rhenish Massif and the Anadjam section in the Moroccan Meseta), we investigated a possible secondary alteration of the magnetic signal, using (1) representative clay mineral assemblages and calibrated illite crystallinity measurements (XRD analyses), (2) major and trace element geochemistry (ICP-AES and ICP-MS analyses) and (3) scanning electron microscopic observations and probe analyses. The detailed measurement protocol of these complementary analyses can be found in Riquier et al (2006Riquier et al ( , 2007. The identification of clay minerals was made according to the position of the (001) series of basal reflections on X-ray diffractograms (Brindley and Brown 1980) and following the protocol defined by Bout-Roumazeilles et al (1999).…”
Section: Complementary Analysesmentioning
confidence: 99%
“…In recent years, a growing number of studies have focused on the use of the magnetic susceptibility (MS) signal as a marker of stratigraphic cycles and paleoenvironmental changes in Paleozoic carbonate rocks (Ellwood et al 1999;Crick et al 2002;Averbuch et al 2005;Hladil et al 2005;Da Silva and Boulvain 2006;Riquier et al 2007;Mabille and Boulvain 2007;Whalen and Day 2008). In these studies, variations in MS have been largely shown to relate to sedimentary facies evolution (Ellwood et al 1999; da Silva and Boulvain 2006;Whalen and Day 2008) and possibly to correlate over long distances within an individual basin or even on the margins of different oceanic realms Ellwood et al 2001).…”
Section: Introductionmentioning
confidence: 99%